"Examen especial a las cuentas ingresos y gastos y su incidencia en la rentabilidad de la empresa Balsablock Cia. Ltda., cantón Quevedo, año 2014" - León Aguilar, Jessica Paola (2016)
The content of the research refers to the results obtained by the implementation of the Special Examination Accounts Income and Expenditure included January 1 to December 31, 2014 the company Balsablock Cia. Ltda., Located in the Windows path, parish San Carlos, the Toquillal enclosure, which has as main economic activity the manufacture and sale of wooden blocks. The Special Review it done in order to check compliance with company policies through the assessment of its internal control system, resulting through the valorization of its components which has a confidence level of 86.50% considered as High Medium, a risk level of 13.50% which is considered low by finding findings as the chart is not the view of workers so that they can visualize the lines of authority; absence of a manual functions to obtain detailed information on the different activities to develop; Contadora does not perform the respective findings of information and does not verify the information entered into the accounting system. In turn it was identified that the company applies the rules for registration of their accounts in accordance with the principles and accounting standards. In reviewing the accounts of income and expenditure ledgers, you could verify the reliability of the information, the horizontal analysis of the income statement where comparisons with the previous year were made was also developed and variations thereof are calculated income and expenses, financial indicators applied to measure the profitability of the company, which was obtained in 2013 and 0.18% in 2014 to 0.15% profit margin, suffering a decline of 0.03%. At the end of the review the Final Report of Special Review with recommendations to improve the management of the accounts of income and expenses it was developed